Adopsi Inovasi Teknik Tanam Jarwo Riting Plus-Plus pada Petani Padi Sawah (Oryza sativa L.) di Kecamatan Susukan Kabupaten Banjarnegara - Fiki Rahmatika; Dumasari Dumasari; Sulistyani Budiningsih (Proceedings Series on Physical & Formal Sciences, 2022)
This research was conducted in Susukan Sub-district, Banjarnegara Regency, from March to April 2022. It aims to figure out the process of the adopted innovation of Jarwo Riting Plus-Plus in the area. The method used is descriptive qualitative and quantitative. They applied purposive sampling method with census technique which resulted in one (1) key informant and 23 farmer respondents who adopted the technique. The research results concluded that Jarwo Riting Plus-Plus is a rice cultivation technique that uses Jajar Legowo system, then a surrounding ditch is made in each rice field, afterwards each rice field is planted with refugia plants, and the last phase is to release of fish in each rice field. Characteristics of 23 respondents include age, number of dependents, education level, length of farming, and land area. The motivating factors for the adoption of the planting technique are institutional support and easy access to information, while the inhibiting factors are farmers' refusal, security intrusion, high land slope, lack of water availability, prone to flooding and high use of fertilizers and pesticides. The adoption rate implemented by the rice farmers in Susukan sub-district is in the medium category.